1994
DOI: 10.3354/dao019215
|View full text |Cite
|
Sign up to set email alerts
|

Role of viruses in the induction of skin tumours and tumourlike proliferations of fish

Abstract: Skin tumours of fish are easily recognizable lesions, some of which have been known for centuries. Causes of fish tumour formation are varied and are often proposed to be multifactorial. In more than half of all cases examined by electron rnicroscopy and virological methods, virus or virus-hke particles were found in tumour tissues. So far, oncogenicity has been clearly demonstrated only for herpesviruses isolated from benign tumours. Classification of fish skin tumours, tumour-associated and turnour-inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 52 publications
(56 reference statements)
0
83
0
Order By: Relevance
“…Similar epithelial and fibro-epithelial tumors in other vertebrate species have also been shown to have viral etiologies (4,9).…”
Section: Etiology and Prevalence Of Gtfpmentioning
confidence: 99%
“…Similar epithelial and fibro-epithelial tumors in other vertebrate species have also been shown to have viral etiologies (4,9).…”
Section: Etiology and Prevalence Of Gtfpmentioning
confidence: 99%
“…number of other tumor types in a wide variety of fishes are suspected of being caused by viruses (Bowser & Casey 1993, Anders & Yoshimizu 1994. However, although peripheral nerve sheath tumors such as neurofibromas, schwannomas and neurofibrosarcomas are relatively common in fishes (Harshbarger et al 1981), none have been shown to be transmissible or to have a viral etiology.…”
Section: Viral Carcinogenesis Has Been Documented In Fishesmentioning
confidence: 99%
“…Epidermal papillomas in masu salmon and in carp have been shown to be caused by herpesviruses (Anders & Yoshimizu 1994). In addition, a …”
Section: Viral Carcinogenesis Has Been Documented In Fishesmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been associated with viral infections [61,118,119], but, for reasons mentioned above, determining whether these apparently benign tumours sometimes progress to malignancy will require studies specifically directed to address this question.…”
Section: Oncogenic Viruses In Reptiles and Fishesmentioning
confidence: 99%